Pelatihan Menulis bagi Peserta Ekstrakurikuler Jurnalistik SMA Negeri 5 Madiun - Wijayanti, Wenny; Adhani, Agnes (Universitas Muria Kudus, 2023)
The purpose of this community service is to provide experience as well as the ability to write, especially prose fiction, for students of SMA Negeri 5 Madiun. Specifically, students who take part in this community service activity are participants in journalism extracurricular activities. Journalistic extracurricular activities at SMA Negeri 5 are called Student Literacy Studios or Sangrila. This community service produces outcomes in the form of increasing students' ability to make prose fiction frameworks.